2014
DOI: 10.1530/eje-13-0673
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in plasma free normetanephrine concentrations: implications for biochemical diagnosis of pheochromocytoma

Abstract: Background: Higher plasma concentrations of catecholamines in winter than in summer are established; whether this impacts plasma concentrations of metanephrines used for the diagnosis of pheochromocytoma is unknown. Objective: In this study, we examined seasonal variations in plasma concentrations of metanephrines, the impact of this on diagnostic test performance and the influences of forearm warming ('arterialization' of venous blood) on blood flow and measured concentrations. Methods: Measurements of plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…2014), previous adrenalectomy (Osinga et al . 2013) and even the season of the year (Pamporaki et al . 2014).…”
Section: Introductionmentioning
confidence: 99%
“…2014), previous adrenalectomy (Osinga et al . 2013) and even the season of the year (Pamporaki et al . 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A separate assay using HPLC showed that plasma norepinephrine levels were altered neither by the diet nor by antibiotic treatment (data not shown), suggesting the effects on normetanephrine were due to changes in norepinephrine metabolism to normetanephrine rather than in plasma levels of its precursor norepinephrine. Seasonal variation in plasma normetanephrine levels were reported . Although this variation was small (i.e., 21% higher in winter than in summer), it resulted in a twofold higher prevalence of false‐positive elevations of normetanephrine in winter than in summer.…”
Section: Discussionmentioning
confidence: 99%
“…Normetanephrine is an O‐methylated metabolite of norepinephrine, used for the diagnosis of pheochromocytoma that secrets large amounts of catecholamines, mostly norepinephrine. It is interesting to find that plasma normetanephrine was depleted after antibiotic treatment, suggesting the intriguing possibility that the production of this metabolite from norepinephrine may entirely depend on gut bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the paper 'Seasonal variation in plasma free normetanephrine concentrations: implications for biochemical diagnosis of pheochromocytoma' published in the March 2014 issue of the European Journal of Endocrinology (1). In that paper, the authors describe w20% higher levels of plasma normetanephrine, a biochemical marker of pheochromocytoma, in the winter, in two cities with northern temperate climate.…”
Section: Dear Editormentioning
confidence: 99%